Solid mensuration : understanding the 3-D space - Earnhart, Richard T. (Quezon City, Philippines : C & E Publishing Inc., 2011)
This book, Solid mensuration - understanding the 3-D space provides a thorough discussion of the subject matter presented in a most concise and simplified approach. From the book PLane and Solid Mensuration - A simplified approach, which Earnhart co-authored, new concepts at introduced and some definitions are modified for easy understanding. To meet the needs of students in solving problems involving geometry, a siginificant number of illustrative examples and exercises have been added. A detailed solution for each example is also provided in this book. Summary tests at the end of each chapter is included to measure the progress of the students in this course. --Richard T. Earnhart--
Chapter 1 Plane Figures -- Chapter 2 Other Plane Figures -- Chapter 3 Polyhedra -- Chapter 4 Prisms and Cylinders -- Chapter 5 Pyramids and Cones -- Chapter 6 Frustums, Truncated Prisms and Cylinders, Prismatoid -- Chapter 7 Spheres -- Chapter 8 Solids of Revolution and Composite Solids.
Includes bibliographical references and index.
Keywords: MEASUREMENT